ACDC Agency: Food and Politics with Community College Students at Vassar - Cowan, Robert (Radical Teacher, 2017)
The food at the All-College Dining Commons (ACDC) at Vassar College stinks. Not that is literally smells foul; it just isn’t very good. The high-achieving community college students in the Exploring Transfer Program (ET) eat breakfast and dinner there for the five weeks that they are studying at Vassar. Ironically, the course I co-taught in ET for two summers, with the Chair of Environmental Studies, is entitled Feast or Famine: Food, Society, Environment. This course is a survey of issues concerning food systems, such as industrial farming, the role of agricultural lobbyists in Washington, overfishing, food sovereignty in developing countries, food stamps, food deserts, the USDA, FDA, WTO, IMF, etc. And yet, with all of the knowledge the students are gleaning from authors like Marion Nestle, Michael Pollan, Wendell Berry and myriad others, they have to eat the crappy food at ACDC. We have had students in this course from Argentina, Bosnia, Bourkina Faso, China, El Salvador, Ghana, Guyana, Haiti, Italy, Mexico, Pakistan, Poland, the Philippines, Sweden, Uzbekistan, and Vietnam. They come from community colleges mostly in the New York area, but also from as far away as Boston, Maine, Los Angeles, and Diné Community College, which is on a Navajo reservation in Northern Arizona. This program—over 30 years old and with over 1,000 alumni—is a sort of academic boot camp for community college students who hope to transfer to an elite liberal arts college, a Research 1 university, or an Ivy League school. It’s a full scholarship program during which they take two courses in five weeks, each team-taught by a community college professor and a Vassar professor. “AC/DC” seems an apt metaphor for the ET program; not for its pop-metal connotations but because of the fact that it demands that students that are accustomed to operating in one current suddenly adjust to quite another. The question that arises out of the experience of eating ACDC, though—of being low-income, immigrant, first-generation college students, studying at one of the whitest and most expensive schools in the country and yet being forced to eat poor food—is “how do they develop a sense of personal agency,” since that is what the transition through community college and onto a school like Vassar requires.